Why I am not a Hindu : - Ilaiah, Kancha (Samya, 2005)
In this manifesto for the downtrodden, the author examines the socio-economic and cultural differences between the Dalitbahujans (the majority, the so-called low castes) and other Hindus in the contexts of childhood, family life, market relations, power relations, Gods and Goddesses, death and, not least, Hindutva (ideology of the Hindu Right).